ETIKOS DUOMENYS (ištrauka) - Spencer, Herbert (Problemos, 2014)
Versta iš: Herbert Spencer. The Data of Ethics. London and Edinburgh: Williams and Norgate, 1879, p. 1–7.The data of Ethics (excerpt)Herbert Spencer>